The Influence of Russian Propaganda on the EU’s Interstate Relations With the Eastern European Countries (Case of Poland-Ukraine) - Ganna, Grabina (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The article is devoted to the analysis of the influence of Russian propaganda on relations between the European Union member states and its eastern neighbors in the case of Poland and Ukraine. The analysis is related to an issue that can be formulated as the following research question: how exactly does propaganda affect domestic and foreign policy processes in countries? A multidisciplinary approach to the study of the impact of political propaganda enabled the use of such methods as: systemic, institutional, structural-functional, content analysis, and descriptive. The article gives definition and main characteristics of the concept of propaganda in political context. Special attention is paid to reasons for the successful use of propaganda by Russia in fanning the conflict in Ukraine, which is presented in the article. The complex of means and methods used in Russia’s information policy to influence Western countries is denoted. The author presents the main narratives of Russian propaganda, and identifies the features of its pressure on interstate relations between Ukraine and Poland by analysing articles in pro-Russian periodicals of Poland and Ukraine. Conclusions are drawn on the need for strong international resistance to Russian propaganda, and to define the shortcomings of the system for countering Russian information aggression in general and propaganda in particular.

Artykuł jest poświęcony analizie wpływu propagandy rosyjskiej na relacje państw członkowskich Unii Europejskiej z sąsiadami na Wschodzie na przykładzie Polski i Ukrainy. Przeprowadzona analiza dotyczy problemu, który może być zdefiniowany w formie zapytania: w jaki sposób może mieć wpływ propaganda na wewnętrzne oraz zewnętrzno-polityczne procesy państw. Wielodyscyplinarne podejście do poznania wpływu propagandy politycznej pozwolił zwrócić się do następujących metod: systemowa, instytucjonalna, strukturalno-funkcjonalna, analiza treści oraz deskryptywna. Artykuł wyznacza pojęcia oraz podstawowe charakterystyki pojęcia propagandy w kontekście politycznym. Szczegółową uwagę przydzielono ujawnieniu przyczyn powodzenia wykorzystania propagandy przez Rosję w celu eskalacji konfliktu na terenie Ukrainy oraz podane są przykłady. Na podstawie analizy artykułów w prorosyjskich publikacjach Polski i Ukrainy, autorka podaje podstawowe narracje propagandy rosyjskiej oraz wyznacza właściwości jej nacisku na międzypaństwowe relacje między Ukrainą a Polską. Wyciąga wnioski o konieczności mocnego międzynarodowego stawiania oporu propagandzie rosyjskiej oraz wyznaczenia wad systemu przeciwdziałania rosyjskiej agresji informacyjnej ogólnie i propagandzie w szczególności.
Wpływ propagandy rosyjskiej na międzypaństwowe relacje Unii Europejskiej z państwami Europy Wschodniej: na przykładzie Ukrainy i Polski
Keywords: European Union; information war; propaganda; information policy; Poland; Ukraine; Russian Federation; Unia Europejska; wojna informacyjna; propaganda; polityka informacyjna; Rzeczypospolita Polska; Ukraina; Federacja Rosyjska